Ovarian endometriosis and fertility preservation problem - Galina E. Chernukha (IP Berlin A.V., 2021)
Aim. To review the most recent literature regarding the modern management of women with ovarian endometriosis and no desire for immediate pregnancy but wanted fertility preservation in future.